SISTEM APLIKASI LOGIKA FUZZY UNTUK PENENTUAN OPTIMASI RAGI TEMPE PADA PROSES FERMENTASI TEMPE KEDELAI MENGGUNAKAN METODE FUZZY MAMDANI (STUDI KASUS : PENGRAJIN TEMPE KEDELAI DESA BULU CINA) - ASPRINA BR SURBAKTI; SHINTA PUTRI RAHAYU; SINEK MEHULI BR PA; RAHELIYA BR GINTING (LP2MTBM MAKARIOZ, 2020)
The main ingredient in the making of Tempe in addition to soy beans is the yeast Tempe. The role of Tempe yeast is veryimportant because the main factor that supports the success of tempeh is optimal yeast levels of the Tempe. In addition, theyeast levels of Tempe can also affect the duration of fermentation. If the level of yeast Tempe and fermentation time can beoptimal then the fermentation process can run well, so it will produce good quality Tempe and decent for consumption.Based on these issues, the author devised an application system built using the Matlab software in which the authors of thisstudy used the fuzzy method and the Matlab GUI as the application's appearance.